Does vitamin E improve the outcomes of pediatric nonalcoholic fatty liver disease? A systematic review and meta-analysis - Sarkhy, AhmedA; Al-Hussaini, AbdulrahmanA; Nobili, Valerio (Saudi journal of gastroenterology, 2014)
To systemically evaluate the efficacy of adjuvant vitamin E on the outcomes of nonalcoholic fatty liver disease (NAFLD) and/or nonalcoholic steatohepatitis (NASH) in children. We searched MEDLINE, PUBMED, EMBASE, the Cochrane Central Register Controlled Trials, and the Cochrane Database of Systematic Reviews over the period between January 1980 and September 2012 for the studies that examined the role of adjuvant vitamin E given at any dose or duration, alone or in combination with other interventions, on the outcome of pediatric NAFLD. The outcomes are alanine aminotransferase (ALT) normalization and histological improvement. Five randomized trials were eligible to be included in our analysis, with a total of 270 participants. There was no statistically significant difference in the effect of adjuvant vitamin E on normalizing serum ALT [risk ratio (RR) =1.18, confidence interval (CI) =0.92-1.53, P = 0.77 for heterogeneity, I2 = 0%]. Sensitivity analysis showed that using higher doses of vitamin E, a longer duration of therapy or adding vitamin C did not change the effect on the measured outcome. Only two studies looked at histological changes as an outcome. We observed substantial heterogeneity between the two studies. Our meta-analysis did not find a significant effect of adjuvant vitamin E over placebo in normalizing serum ALT. Data on the long-term effect of adjuvant vitamin E on histological improvements in NAFLD patients are still lacking. Larger, well-designed randomized controlled trials (RCTs) in children with histological endpoints are still needed to answer this question.